Pedagogical Approaches To The Development System Of Artistic Culture Of Individual - Gabdullovna Akhmetshina, Elmira (2017)
In this article we consider the most significant pedagogical approaches that are applied in the pedagogical system of the development of the artistic culture of the individual that we have developed.Educational concepts, training programs on various types of creative activity were developed and tested. The main method that we used in the analysis of the effectiveness of the pedagogical process aimed at mastering the fine arts is the analysis of the products of creative activity, i.e. art works performed by students. We have identified, studied and tested in the educational process such approaches as: system approach (the pedagogical system of the development of the artistic culture of the personality), interactive approach (interaction between teacher and student), the facilitation approach (the organization of the creative environment), the integrative approach (multicultural, synthesis of arts), the differentiated approach (individual). The conducted researches have shown high efficiency of application of the specified approaches in training to the fine arts. The article reveals the main results of theoretical research, confirmed in the course of the experiment.